Intestinal translocation of clinical isolates of vancomycin-resistant Enterococcus faecalis and ESBL-producing Escherichia coli in a rat model of bacterial colonization and liver ischemia/reperfusion injury. - Karin M van der Heijden (Public Library of Science (PLoS), 2014)
The objectives of this study were to develop a rat model of gastrointestinal colonization with vancomycin-resistant Enterococcus faecalis (VRE) and extended-spectrum beta-lactamase (ESBL)-producing E. coli and to evaluate intestinal translocation to blood and tissues after total and partial hepatic ischemia. Methods - We developed a model of rat colonization with VRE and ESBL-E coli. Then we studied four groups of colonized rats: Group I (with hepatic pedicle occlusion causing complete liver ischemia and intestinal stasis); Group II (with partial liver ischemia without intestinal stasis); Group III (surgical manipulation without hepatic ischemia or intestinal stasis); Group IV (anesthetized without surgical manipulation). After sacrifice, portal and systemic blood, large intestine, small intestine, spleen, liver, lungs, and cervical and mesenteric lymph nodes were cultured. Endotoxin concentrations in portal and systemic blood were determined. Results - The best inocula were: VRE: 2.4×10(10) cfu and ESBL-E. coli: 1.12×10(10) cfu. The best results occurred 24 hours after inoculation and antibiotic doses of 750 µg/mL of water for vancomycin and 2.1 mg/mL for ceftriaxone. There was a significantly higher proportion of positive cultures for ESBL-E. coli in the lungs in Groups I, II and III when compared with Group IV (67%; 60%; 75% and 13%, respectively; p:0.04). VRE growth was more frequent in mesenteric lymph nodes for Groups I (67%) and III (38%) than for Groups II (13%) and IV (none) (p:0.002). LPS was significantly higher in systemic blood of Group I (9.761 ± 13.804 EU/mL-p:0.01). No differences for endotoxin occurred in portal blood. Conclusion -We developed a model of rats colonized with resistant bacteria useful to study intestinal translocation. Translocation occurred in surgical procedures with and without hepatic ischemia-reperfusion and probably occurred via the bloodstream. Translocation was probably lymphatic in the ischemia-reperfusion groups. Systemic blood endotoxin levels were higher in the group with complete hepatic ischemia.